Digitalization and the shifting religious literature of Indonesian Muslims in the Era of Society 5.0 - Ichwan, Moh. Nor; Amin, Faizal; Khusairi, Abdullah; Andrian, Bob (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
The advent of science and technology, which has resulted in the digitalization of the Indonesian Muslim community during the Industrial Revolution 4.0 and the advent of Society 5.0, has prompted a shift in the religious literature of Indonesian Muslims. This research aims to examine the impact of digitalization in the post-truth era on the behavior of Muslims who tend to seek solutions to their religious problems outside the traditional religious authority. The data sources for this study were collected through observation, interviews, and a review of relevant literature in the form of documents or online data. In terms of socio-religious factors, this research identified three key elements that have contributed to the shift in the religious literature of Indonesian Muslims from the ulama to social media. Firstly, the internet and social media provide Muslims with convenient access to information and resources that can address their daily religious concerns promptly and effectively. Secondly, the rise in community religious activity has not been accompanied by a corresponding increase in digital literacy, particularly in the use of social media. Thirdly, the solutions to religious problems obtained by Muslims through social media are immediate, leading to a less comprehensive and more partial understanding of Islam. Digitalization has led Indonesian Muslims to be more pragmatic in search of religious meaning. ***** Perkembangan ilmu pengetahuan dan teknologi yang bermuara pada digitalisasi di era Revolusi Industri 4.0 menuju Society 5.0 saat ini telah menggeser literatur keagamaan umat Islam Indonesia. Penelitian ini bertujuan mengkaji dampak digitalisasi di era post-truth terhadap prilaku umat Islam yang cenderung meninggalkan ulama dalam menyelesaikan masalah keagamaan yang dihadapinya. Sumber data dalam penelitian ini dikumpukan melalui observasi, wawancara, dan studi pustaka yang berupa dokumen atau data online. Secara sosio-religius, penelitian ini menemukan tiga aspek penting yang menjadi sebab pergeseran literatur keagamaan umat Islam Indonesia dari ulama ke media sosial. Pertama, mudahnya akses internet dan media sosial yang mampu menjawab secara cepat dan efisen atas problem yang dihadapi oleh umat Islam sehari-hari. Kedua, meningkatnya geliat kagamaan masyarakat yang tidak dibarengi dengan pemahaman yang baik tentang literasi digital dalam bentuk media sosial. Ketiga, solusi atas problem keagamaan yang diperoleh umat Islam melalui media sosial bersifat instan sehingga mengakibatkan pemahaman masyarakat atas agama Islam menjadi tidak kompehensif dan lebih bersifat parsial. Digitalisasi telah menyebabkan umat Islam Isndonesia menjadi lebih pragmatis dalam mencari makna dan pesan keagamaan.